Two cleavage products of the Drosophila accessory gland protein ovulin can independently induce ovulation. - Heifetz, Y.; Vandenberg, L.N.; Cohn, H.I.; Wolfner, M.F. (Proceedings of the National Academy of Sciences of the United States of America, 2005)
Proteins and peptides in Drosophila melanogaster seminal fluid induce mated females to increase their rates of egg deposition. One seminal-fluid protein, ovulin (Acp26Aa), stimulates an early step in the egg-laying process, the release of oocytes by the ovary. Ovulin, upon transfer to females, is cleaved sequentially within the mated female's reproductive tract. Here, we show that systemic ectopic expression of ovulin is sufficient to stimulate ovulation in unmated females. By using this assay to assess the functionality of ovulin's cleavage products, we find that two of the four cleavage products of ovulin can stimulate ovulation independently. Thus, ovulin's cleavage in mated females is not destructive and instead may liberate additional functional products with potential to modulate ovulation independently.